Assessment Of Pre-Service Teachers’ Perceived Usefulness, Ease of Use and Behavioural Intention to Use ICTs for Mathematics Instruction: A Case Study - Olutayo Toyin Omole (USN Kolaka, 2022)
The need to enhance mathematics instruction through the use ICTs for improving the performance of students in the subject in Nigeria can no longer be paid lip service. ICTs have proven to be a veritable instrument that can actively engage and improve students’ mathematical learning experience. This study examined preservice teachers’ perceived usefulness, ease of use and behavioural intention to use ICTs for mathematics instruction in Nigeria. The study adopted a descriptive research design of a survey type and 315 students who enrolled in a college of education to become mathematics teachers were selected through a multi-stage sampling technique. Data was collected through a self-designed questionnaire and the generated data were analysed using frequency counts, simple percentages, mean and standard deviation. Results reveal among others that preservice teachers’ perception of the usefulness of ICTs to enhance mathematics instruction is very high. Equally, their perceived ease of use of ICTs for mathematics instruction is high. Power supply, lack of fast internet connection and high fees for internet access were perceived by the preservice teacher as the greatest challenge to the effective use of ICTs for mathematic instruction. The conclusion of the study was therefore drawn based on the results of the study